PENGARUH UKURAN PERUSAHAAN, RETURN ON ASSETS, LEVERAGE, KOMITE AUDIT DAN SALES GROWTH TERHADAP TAX AVOIDANCE (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2015) - Sofi Ariyanti, 13.05.52.0068; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2017)
This study aimed to examine the effect of firm size, ROA, leverage, audit committes, and sales growth against tax avoidance. This study focused on manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period 2013-2015. This study 180 number of observations sample obtained by the method nonprobability sampling purposive sampling technique. The analysis technique used in this research is multiple linear regression analysis. The analysis showed that the size of the company, ROA, leverage, audit committes has no effect on tax avoidance. Sales growth has positive effect on tax avoidance.Keywords:Â Tax Avoidance, Firm Size, ROA, Leverage, Audit Committes, and Sales Growth